Figural frieze on the back side wall of the temple - Temples of India Project Team (Jio Institute, 2024)
The three sides of the main garbhagriha (sanctum sanctorum) of this small shrine have five sculptures each. Seen here is the figural frieze on the back side wall of the temple. Here are dikpalas (deities for cardinal directions) on the corner of offsets, apsaras or surasundaris (celestial damsels) in the intermediary projections. The three principal projections on three sides contain images of Chamunda, Natesha or dancing Shiva and Lakulisha. The style of sculptures matches with other Paramara period icons. This pattern of carving dikpalas, apsaras and deities from the Shaiva pantheon is unique and found at several structures within Arthuna.